A survey on anxiety disorders among seniors of the University of the Philippines Tacloban College - Arceño, Sharon G. (Sharon G. Arceño, 1998)
The study aimed to determine if there are senior students in UP Tacloban College who have anxiety disorders. A total of 50 participants were randomly selected, 25 are males and 25 females. The subjects were divided among the courses offered by the College. The questionnaire was used to gather the needed data. After retrieval of the questionnaires, the researcher tabulated the data. The results show that since obtained t = 0.87 which is greater than 2.16 at .05 level, it is not significant, thus the null hypothesis is accepted that there is no difference between the anxiety proneness between male and female respondents. It also revealed that a person may exhibit symptoms of different anxiety disorders at the same time. From the findings, it can be derived that there are seniors who have anxiety disorders. The disorders most of the participants suffer are from panic disorder, specific and social phobias, GAD, obsessive-compulsive disorder and PTSD. Recommendations on how to deal with anxiety problems are given.